14-8x+6-5x=10+2x-5

Simple and best practice solution for 14-8x+6-5x=10+2x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-8x+6-5x=10+2x-5 equation:


Simplifying
14 + -8x + 6 + -5x = 10 + 2x + -5

Reorder the terms:
14 + 6 + -8x + -5x = 10 + 2x + -5

Combine like terms: 14 + 6 = 20
20 + -8x + -5x = 10 + 2x + -5

Combine like terms: -8x + -5x = -13x
20 + -13x = 10 + 2x + -5

Reorder the terms:
20 + -13x = 10 + -5 + 2x

Combine like terms: 10 + -5 = 5
20 + -13x = 5 + 2x

Solving
20 + -13x = 5 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
20 + -13x + -2x = 5 + 2x + -2x

Combine like terms: -13x + -2x = -15x
20 + -15x = 5 + 2x + -2x

Combine like terms: 2x + -2x = 0
20 + -15x = 5 + 0
20 + -15x = 5

Add '-20' to each side of the equation.
20 + -20 + -15x = 5 + -20

Combine like terms: 20 + -20 = 0
0 + -15x = 5 + -20
-15x = 5 + -20

Combine like terms: 5 + -20 = -15
-15x = -15

Divide each side by '-15'.
x = 1

Simplifying
x = 1

See similar equations:

| 6x+18=116-6x | | (x+2)(2-x)=6x-x | | 2x+36=21x-36 | | 17-6x=4x-8 | | 9-5k+2k=k-23 | | x^2+4x-1=9x-5 | | 6x+30=13-33 | | x^2+8x-2=7 | | x^2-(a+2b)x+b^2+ab=0 | | 24a=36 | | 12-x=30-4x | | 3x+4=5x-16 | | x^2+32x-196=0 | | x-17=6x+8 | | 9x-5=x+19 | | 9x+6=6x+10 | | 7x-20=04-3x | | 7(2x-5)=42 | | 21-7x=10+4x | | x+2=-3x+30 | | (5x-3)*2+(2x+1)*2=34 | | .4x=-5.3 | | 2x+12=4x+2 | | 10-8=30-15x | | 5x+4y+5z-2x+2z-6y= | | 6x+36=8x+20 | | (x+1)*(2x-6)=0 | | 285-4x=41x+20 | | -15+x=x+18 | | 10-7x=170-35x | | 149-7x=20x+20 | | a-6=-21 |

Equations solver categories